Nilai-Nilai Keikhlasan dalam Al-Qur'an untuk Pengembangan Etos Kerja: Perbandingan dengan Teori Self-Determination - Ahmad, Naufal Hafiid; Rofiah, Nur; Tamam, Badru (Jawa Timur: Prodi. Ilmu Al Quran dan Tafsir Fakultas Ushuluddin IAI Tarbiyatut Tholabah, 2024)
This study aims to analyze the values of sincerity (ikhlas) in the Qur'an and their contribution to the development of work ethics by comparing them with the Self-Determination Theory (SDT) from Western psychology. The research employs a qualitative approach with a descriptive-analytical method, involving the interpretation of Qur'anic verses about sincerity and an analysis of SDT, which emphasizes autonomy, competence, and relatedness as key aspects of motivation. The findings reveal that the Qur'an provides a spiritual foundation through the values of sincerity, where pure intention to seek Allah's pleasure serves as the primary basis for all actions. This concept focuses on selfless contribution, surpassing material orientation. In contrast, SDT highlights intrinsic motivation derived from individuals' psychological needs, such as autonomy and competence. While both share similarities in terms of internal motivation, the values of sincerity in the Qur'an offer a deeper spiritual dimension, making it a holistic approach to fostering meaningful work ethics. This study concludes that implementing the values of sincerity can significantly enhance work motivation with a higher orientation toward spiritual goals, surpassing secular approaches. These findings contribute significantly to the development of more holistic work ethics in the context of Islam.